2016
DOI: 10.1007/s00441-016-2427-5
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic zonation of liver polyploidy

Abstract: The liver is a polyploid organ, consisting of hepatocytes with one or two nuclei each containing 2, 4, 8 or more haploid chromosome sets. The dynamic changes in the spatial distributions of polyploid classes across the liver lobule, its repeating anatomical unit, have not been characterized. Identifying these spatial patterns is important for understanding liver homeostatic and regenerative turnover, as well as potential division of labor among ploidy classes. Here, we use single molecule-based tissue imaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
48
2
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 25 publications
8
48
2
4
Order By: Relevance
“…Moreover, it should be noted that the number of nuclei visible in the optical microscope using routine histological sections is completely different from the cell ploidy hepatocytes assessed using advanced methods, such as single molecule fluorescence in situ hybridization. Hepatocytes with one or two nuclei may contain two, four, eight or even more haploid chromosome sets (Tanami et al 2016). In contrast to our findings (4% of BnHEP), Vinogradov et al (2001) reported in pig of unknown age that 54% of binuclear hepatocytes had 2 9 2c ploidy.…”
Section: Size Density and Fraction Of Bnhep Exhibit Considerable Intcontrasting
confidence: 99%
See 1 more Smart Citation
“…Moreover, it should be noted that the number of nuclei visible in the optical microscope using routine histological sections is completely different from the cell ploidy hepatocytes assessed using advanced methods, such as single molecule fluorescence in situ hybridization. Hepatocytes with one or two nuclei may contain two, four, eight or even more haploid chromosome sets (Tanami et al 2016). In contrast to our findings (4% of BnHEP), Vinogradov et al (2001) reported in pig of unknown age that 54% of binuclear hepatocytes had 2 9 2c ploidy.…”
Section: Size Density and Fraction Of Bnhep Exhibit Considerable Intcontrasting
confidence: 99%
“…It may be hypothesized that the peripheral parts of the liver lobes represent the developmentally oldest hepatic regions and thus contain more large polyploid cells. Tanami et al (2016) mapped the zonation of liver polyploidy in rat, revealing that liver polyploidy proceeds in spatial waves, advancing more rapidly in the midlobule zone than the periportal and perivenous zones. The The smallest numerical density of hepatocytes N V (HEP) was identified in the peripheral regions of the liver.…”
Section: Peripheral Regions Of Hepatic Lobes Contain the Largest Mnhementioning
confidence: 99%
“…We observed a 1.3-times relative enrichment of 4n hepatocytes in the pericentral cluster, indicating that they reside close to the central vein. This is in agreement with recent studies in which polyploid hepatocytes have been preferably located by histological analysis in the pericentral zone, and diploid hepatocytes in the periportal zone using cell-lineage tracing [77,108].…”
Section: Hepatic Metabolic Zonation Determines Gene Expression Levelssupporting
confidence: 92%
“…Furthermore, the broad spatial heterogeneity in the liver shows that key liver functions are zonated [9], and recently it has been shown that the zonation can be perturbed during liver fibrosis [14,15]. In this context, the spatial distribution of polyploid hepatocytes and its functional consequences are still in debate [8,40,77,85,108]. We used diffusion pseudotime to infer the pseudospatial ordering of 2n and 4n hepatocytes according to defined markers of liver zonation, and we found that 4n nuclei are distributed throughout the hepatic lobe with an enrichment in the pericentral zone (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse Axin2‐labeled perivenous hepatocytes are two‐thirds diploid and one‐third tetraploid, whereas other lobular hepatocytes are mostly polyploid, reflecting the proliferative potential of perivenous cells in hepatic homeostasis (Wang et al, ). Tanami et al () found a relatively higher abundance of diploid hepatocytes in both the perivenous and periportal zones of mice, assessed by nuclear staining with DAPI and smFISH for Pck1. The midlobular zone is enriched with polyploid hepatocytes, and the rate of polyploidization there is higher than in other lobular zones.…”
Section: Ploidy Classes Of Perivenous Hepatocytesmentioning
confidence: 99%